PENGARUH FAKTOR-FAKTOR KOMPETENSI TERHADAP KINERJA KARYAWAN JASA KONSULTANSI KONSTRUKSI DI PEKANBARU - maharani, lola (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2019)
This study aims to analyze the influence of competency factors on performance. The location of this research was conducted in Pekanbaru. While the time of the study was conducted January 1, 2016 until February 28, 2016. The source of this research data is the Construction Consultancy Services Employee in the city of Pekanbaru. With 87 respondents as the research sample. Data analysis techniques in the form of descriptive analysis, validity and reliability test, classic assumption test (normality test, autocorrelation test, multicollinearity test, heterokedacity test), and hypothesis testing namely t test (partially), F test (simultaneous test) and test coefficient of determination). The results of this study are partial; Knowledge (X1), Skills (X2), Self Concept (X3) and Personal Characteristics (X4) influence Employee Performance (Y) construction consulting services in Pekanbaru city. And Simultaneously Knowledge (X1), Skills (X2), Self Concept (X3) and Personal Characteristics (X4) affect Employee Performance (Y) construction consulting services in Pekanbaru city